An analysis of the underwater gliding motion in collegiate competitive swimmers - Wada, T.; Sato, T.; Ohishi, K.; Tago, T.; Izumi, T.; Matsumoto, T.; Yamamoto, N.; Isaka, T.; Shimoyama, Y. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The underwater gliding motion during start and turn phases are important for the total race time in modern swimming.The purpose of this study was to analyze the underwater gliding motion in collegiate competitive swimmers. Twelve male collegiate swimmers were monitored with a video camera (SK-2130, SONY, Japan) with a sampling frequency of 60Hz in the sagittal plane to measure the angular displacement of their different joints. A motion analysis system (Frame-DIAS4, DKH, Japan) was used to digitize ten body landmarks. The following results were obtained: the highest speed was maintained during the gliding motion when the knee and the hip joint angles of 180 degrees were maintained from push off from the wall to 0.8sec (1.82m). In addition, swimming speed slowed down when the involuntary movements of flexion-extension in the knee and the hip joints were observed during the gliding motion.